Development history and prospect of remote sensing technology in coal geology of China - Kelong Tan; Junwei Qiao (International Journal of Coal Science & Technology, 2020)
Abstract Coal remote sensing technology was founded in the period of coal resources survey after the founding of People’s Republic of China. Aerophoto Grammetry & Remote Sensing Bureau of China National Administration of Coal Geology was established, specializing in the application and promotion of coal remote sensing technology. With the rapid development of coal geological exploration in China, coal remote sensing technology has evolved from coal geology based survey to comprehensive survey that factors in resources, environment, ecology and so on. This paper summarizes the general situation, theories, development process, key research and future of remote sensing technology for coal mining in China. Spanning over 50 years, the history of China’s coal remote sensing technology can be divided into five stages: aero-geological mapping, coal remote sensing theory experimental research, application research and promotion, architecture planning and productionisation, “3S” technology integration and application. This paper expounds the main technical progress, application fields, major projects and major achievements in various historical periods, and points out that the coal remote sensing has entered a unified development stage of “Aviation, Aerospace and Ground”, with a focus on high-resolution remote sensing, hyperspectral remote sensing, radar remote sensing, “3S” technology integration and multi-means comprehensive exploration and evaluation. In the future, coal remote sensing technology will develop rapidly in data mass, technology integration, evaluation intelligence, integration application programming, system visualization, etc. Coal remote sensing technology has entered the industrial development from technology application.